Exploring the Evolution of Queer Pedagogy Research: A Bibliometric Study of Inclusive Education - Dina Destari; Siti Aisyah Hanim; Istiarsyah Istiarsyah (The Eastasouth Journal of Learning and Educations, 2025)
This study explores the intellectual structure and thematic evolution of queer pedagogy research within the context of inclusive education through a bibliometric analysis. Drawing on publication data from the Scopus database (2000–2024), the study employs VOSviewer to analyze co-authorship patterns, keyword co-occurrence, and citation networks. The findings reveal that queer pedagogy is a vibrant and interdisciplinary field grounded in critical theory and post-structural thought, with core concepts such as heteronormativity, critical pedagogy, and intersectionality at its center. Over time, the field has expanded to include newer themes such as reflexivity, ecopedagogy, and autoethnography, indicating methodological diversification and broader sociopolitical engagement. The study also identifies a concentration of scholarly activity in Western academic institutions, highlighting both the strength and the representational limitations of current research landscapes. By visualizing key trends, influential authors, and underexplored areas, this study provides a comprehensive map of queer pedagogy’s scholarly development and offers insights for advancing inclusive educational practices.